Confessions of a prairie bitch eaudiobook How i survived nellie oleson and learned to love being hated. - Arngrim, Alison (Tantor Media, 2017)
Confessions of a Prairie Bitch is Alison Arngrim's comic memoir of growing up as one of television's most memorable characters—the devious Nellie Oleson on the hit television show Little House on the Prairie . With behind-the-scenes stories from the set, as well as tales from her bohemian upbringing in West Hollywood and her headline-making advocacy work on behalf of HIV awareness and abused children, Confessions of a Prairie Bitch is a must for fans of everything Little House : the classic television series and its many stars like Michael Landon and Melissa Gilbert; Gilbert's bestselling memoir Prairie Tale ; and, of course, the beloved series of books by Laura Ingalls Wilder that started it all.